Analisis Permintaan Kredit Pensiun Pada Bank BTPN Cabang Pekanbaru - Ardiansyah Siregar; Anthony Mayes; Rosyetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to analyze the Pension Credit Demand in BTPN held in Pekanbaru of Riau Province. The population in this study is the Bank Pekanbaru City Bank customers who make pension credit loan people amounted to 1,688 customers, samples are taken using Slovin formula with the results of the sample amounted to 95 customers. Data analysis techniques in this study by using Quantitative Descriptive Method models performed in this study is the Multiple Linear Regression there are some tests performed in this study: Classical Test Assumptions, Multicollinearity Test, Test heterocedastity, autocorrelation test, Normality Test, Test of Significance, Test t Test, F-acquired research F.Hasil count (58,059)> F table (3,095) and sugnifikansi (0,000) <0.05 means that the income and interest rates positive effect on the demand for pension credit BTPN Pekanbaru. While known t count of -1.718 with a significance of 0.089. Thus t (-1.718) <t table (1.986) and significant (0.089)> 0.05 means that the interest rate does not affect the demand for credit. Based on observations made observations most consumers just do not know how much the interest rate offered by the Bank and the Bank Pekanbaru they do not want to know the amount of mortgage interest rates being offered, this is because not all serve Bank of pension credit, which has only BTPN services Retirement credit.Keywords: Demand for Loans, Income, Interest Rates, Pension Credit